Predictors of doping intentions in elite-level athletes: A social cognition approach - Lazuras, L.; Barkoukis, V.; Rodafinos, A.; Tsorbatzoudis, H. (Journal of Sport & Exercise Psychology, 2010)
Doping use is an ongoing problem in contemporary sports. Despite efforts to detect and control doping, research on its etiology is limited, especially among elite-level athletes. The present study used an integrated social cognition model to examine the predictors of doping intentions. Structured anonymous questionnaires were completed by 1075 Greek adult elite-level athletes (M age = 25 years, SD = 5.89, 36.1% females) from both team and individual sports. Multiple regression and mediation analyses showed that attitudes, normative beliefs, situational temptation, and behavioral control significantly predicted doping intentions. A normative process was identified whereby situational temptation mediated the effects of normative beliefs on intentions. The findings provide the basis for future social cognition research in doping use, and set the framework for the development of evidence-based preventive interventions.